Conducting Qualitative Research in an International and Distributed Research Team: Challenges and Lessons Learned - Prikladnicki, R.; Evaristo, R.; Damian, D.; Audy, J.L.N. (Proceedings of the 41st Annual Hawaii International Conference on System Sciences (HICSS 2008), 2008)
In this paper, we discuss challenges for planning and executing qualitative research conducted by an international research project team. The study comprised an exploratory examination of strategies of offshoring and onshoring for software development. An important methodological challenge is that the members of the research team live in different countries, rely on different languages and originate from different cultures. These challenges are in many ways analogous to those inherent in the subject we are researching, distributed software development. To explore these issues, we present the difficulties we faced on collecting and analyzing the qualitative data. Our main contribution is the identification of challenges, strategies to overcome them, and a set of lessons learned.